Effects of active video games on parent-child relationships among overweight and obese adolescents in China: a pilot study - Mai, Yiqiang; Soh, Kim Geok; Abu Saad, Hazizi (2222-6990, 2024)
The purpose of this study is to explore the effect of AVG intervention on the parent-child relationships of overweight and obese male adolescents under a family-based parental involvement model. A cluster randomised controlled trial (C-RCT) was conducted with 12- to 14-year-old participants, divided into three groups: (1) Parental Involvement in Active Video Games (PIAVG), (2) Single Player Active Video Games (SPAVG), and (3) Control (watching TVWTV). The intervention lasted for two weeks, during which changes in parent-child relationship levels were assessed at baseline and post-intervention. Although no significant changes were observed within the three groups, the trend analysis indicated an upward trajectory in both experimental groups. Notably, the PIAVG group demonstrated significantly more improvement in the measured outcomes than the WTV group in the inter-group comparison. The findings suggest that parental involvement in active video games enhances the effectiveness of such interventions, leading to better parent-child relationships among overweight and obese adolescents. This underscores the potential for family-based interventions to combat adolescent obesity in this population.